2021
DOI: 10.1021/acs.jpcc.1c03497
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Size Effects on the Crystallographic Structure and Magnetic Properties of RMnO3 (R = Eu, Gd, Tb, Dy) Nanoparticles

Abstract: We synthesized lanthanoid manganese oxide RMnO 3 (R = Eu, Gd, Tb, and Dy) nanoparticles with particle sizes ranging from approximately 6.5 to 23 nm and investigated both their crystal structure and magnetic properties. The RMnO 3 nanoparticles showed a strong correlation between crystal structure and magnetic properties, and particle size effects on these properties vary owing to the different atomic radii of the lanthanoid ions. The magnetic properties of all of the nanoparticles exhibited significant changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Nanoparticles of strongly correlated materials, particularly manganese oxides, such as RMnO 3 (R = rare earth) and Mn 3 O 4 , are expected to exhibit characteristic size effects on the crystal structure and magnetic properties owing to the strong coupling between the spin, orbital, and lattice. Our previous investigations of rare earth manganese oxide RMnO 3 and DyMn 2 O 5 have found that the characteristic size dependences of the magnetic properties and crystallographic structures are related to the strong correlation between the crystal structure and the magnetic properties. Moreover, nanoparticles of magnetically frustrated materials are expected to exhibit characteristic size effects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nanoparticles of strongly correlated materials, particularly manganese oxides, such as RMnO 3 (R = rare earth) and Mn 3 O 4 , are expected to exhibit characteristic size effects on the crystal structure and magnetic properties owing to the strong coupling between the spin, orbital, and lattice. Our previous investigations of rare earth manganese oxide RMnO 3 and DyMn 2 O 5 have found that the characteristic size dependences of the magnetic properties and crystallographic structures are related to the strong correlation between the crystal structure and the magnetic properties. Moreover, nanoparticles of magnetically frustrated materials are expected to exhibit characteristic size effects.…”
Section: Introductionmentioning
confidence: 98%
“…Mesoporous silica MCM-41 and SBA-15, which have one-dimensional pores, are a popular mesoporous material for synthesizing magnetic nanoparticles . In our previous study, RMnO 3 (R = La, Eu, Gd, Tb, and Dy), DyMn 2 O 5 , and NiO nanoparticles embedded in SBA-15 were successfully synthesized and their crystal structures and magnetic properties were investigated. , A mesoporous sulfonated styrene-divinylbenzene copolymer template also was used to produce stable and size-controllable Fe 3 O 4 nanoparticles . In this case, the size control of Fe 3 O 4 nanoparticle was achieved through the change of the ferrous ion concentration incorporated in the polymeric template.…”
Section: Introductionmentioning
confidence: 99%
“…EuInO 3 is isostructural with GdInO 3 , belonging to the hexagonal structure. , However, the ferroelectricity of EuInO 3 is still ambiguous due to the absence of EuInO 3 single crystals. Only a few studies have reported EuInO 3 polycrystals. ,, Obtaining large single crystals is very important for a detailed investigation by many probes. In order to explore the relationship between the structure and physical properties of EuInO 3 , the EuInO 3 single crystal has been grown by the laser floating zone method in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite nanoparticles (Fe 3 O 4 NPs) have attracted attention for various biomedical fields due to their strong magnetic properties and excellent biocompatibility. Recent studies have shown the advantages of Fe 3 O 4 NPs in many biomedical applications such as localized drug delivery, magnetic resonance imaging (MRI), and hyperthermia. However, the high surface energy of NPs typically induces aggregation, which causes difficulties in controlling the size and shape of NPs, significantly affecting the magnetic property. Additionally, the magnetite is easily oxidized to other thermodynamically stable structures [e.g., maghemite (γ-Fe 2 O 3 ) or hematite (α-Fe 2 O 3 )] in the atmosphere, which leads to the reduction of magnetic saturation . Surface modification in the synthetic field can reduce the surface energy of NPs and enhance the steric hindrance between NPs, thus preventing the aggregation.…”
Section: Introductionmentioning
confidence: 99%